PEMBELAJARAN MENEMUKAN UNSUR-UNSUR INTRINSIK HIKAYAT MELALUI MODEL STUDENT TEAMS ACHIVEMENT DIVISIONS (STAD) - Mei Ekawati, author (JURNAL PESONA, 2015)
Reading is one of the important aspects in the process of communicating. Students have the potential to read. One of them read a work of literature, that saga. The success saga of learning to read will depend on the role of teachers, namely the use of learning methods and techniques are appropriate. This study used quasi-experimental methods (quasi experimental research). This research method starts with trial (trial), so that the data obtained is taken based on the test results. Based on the analysis conducted, obtained the degrees of freedom of 32 with 95% confidence level, it>, ie 10.2> 2.04. This means that there is a significant difference between pretest and posttest in class X MA Bahrul Ulum in learning discover the intrinsic elements of the saga through a model student teams achievement divisions. This shows, that the model student teams achievement divisions used in learning proper finding intrinsic elements saga.Keywords: Learning, Intrinsic Elements, Saga, Model STAD